Pojęcie „talent” w wybranych wypowiedziachwspółczesnego Kościoła - Grochowski, Grzegorz (Warszawskie Studia Teologiczne, 2019)
Since the dawn of time people have been searching for an answer to the question of what is the source of individual differences between people and their diverse ability to meet challenges of broadly understood development. For a long time, the concept of talent, derived from the popular Gospel parable, has been associated with the issue of human aptitude (Matt. 25: 14-30). The purpose of this article was to investigate the meaning of the word talent and the contexts for its use in contemporary teaching of the Roman Catholic Church. Two basic understandings of the word were analyzed - spiritual and colloquial. Then, the article investigates the areas in which Christians were multiplying their talents: the Church, social and political life, culture, work and economic activity, science and technology, education, family and upbringing. The article examines the attitude a Christian should take towards his own talent and what obstacles he must overcome to improve his abilities. As a result of the analysis, theological and pastoral thesis were stated and some possible applications of the concept of talent in the area of Christian pedagogy, catechism and the broadly understood ministry of the word in the Church were indicated.